Draft Annual Plan 2001-2002 Government of Tripura Planning Department - Planning Commission (Planning Commission, 2001)
Agriculture and Allied Activities, Rural Development, Special Area Programmes, Irrigation and Flood Control, Energy, Industry and Minerals, Transport, Communications, Science Tech. and Environment, General Economic Services, Social Services, General Services
Draft Annual Plan 2001-2002
Government of Tripura